S-nitrosothiols and reactive oxygen species in plant disease resistance and development - Brzezek, Kerstin (The University of Edinburgh, 2014)
Nitric oxide (NO) as well as reactive oxygen species (ROS) play an important role in defence signalling in plants. After successful recognition of an invading pathogen, an increase in ROS occurs, the ’oxidative burst’; and a ’nitrosative burst’ is also observed. This leads to the induction of defence responses, including the ’hypersensitive response’ (HR), a form of programmed cell death. A balanced production of hydrogen peroxide and NO is crucial for HR induction. In a process called S-nitrosylation, NO can react with cysteine thiols to form S-nitrosothiols, or react with glutathione to form S-nitrosoglutathione (GSNO). The enzyme GNSO reductase (GSNOR) indirectly regulates SNO levels by turning over GNSO. The Arabidopsis thaliana T-DNA insertion mutant atgsnor1-3 shows a complete loss of GNSOR activity and has drastically increased SNO levels, resulting in stunted growth, loss of apical dominance, increased HR, loss of salicylic acid (SA) accumulation and increased susceptibility to avirulent, virulent and non-host pathogens. Two recessive and allelic EMS suppressor mutants in the atgsnor1-3 background were isolated, which showed mostly wild type growth. The mutations were identified by map-based cloning as two different point mutations in At1g20620 or CAT3, one of three catalase genes in Arabidopsis. Catalases break down hydrogen peroxide, with CAT2 being the major catalase in Arabidopsis. All three catalases are structurally very similar, but show temporal and spatial differences in their expression patterns. The suppressor mutants recovered apical dominance, and partially recovered disease resistance to avirulent pathogens, but were still susceptible to virulent pathogens and showed decreased SA levels. The suppressor mutants showed wild type HR in response to different avirulent bacteria. Interestingly, loss-of-function of the other catalase genes as well as loss-of-function of other redox-related genes did not restore apical dominance of atgnsor1-3 plants. This effect seems to be highly specific to CAT3, possibly because of its expression pattern or its expression levels. Further research is needed to fully understand the mechanisms at work here, but these results certainly seem to show a direct connection between redox signalling and S-nitrosylation.
Keywords: S-nitrosylation; plant defence; reactive oxygen species